Electrocatalytic Reduction of Carbon Dioxide on Conducting Glass Electrode Modified with Polymeric Porphyrin Films Containing Transition Metals in Ionic Liquid Medium - Aguirre-Quintana, M; Aguirre-Quintana, M (Taylor and Francis Ltd., 2014)
Electrocatalytic reduction of carbon dioxide has been studied using modified electrodes with conducting polymers from tetra-amino-phenyl porphyrins containing transition metals (Zn(II) and Fe(III)), on an indium tin oxide electrode in BMImBF4, as solvent and supporting electrolyte. Electropolymerized Fe porphyrin is active toward the reaction under survey, while Zn derivative shows poor activity. Spectroelectrochemistry experiments on electropolymerized Fe porphyrin films have shown intermediary species like Fe-CO2 and Fe-CO at open-circuit potential. Potential-controlled bulk electrolysis carried out in ionic liquid shows that only carbon monoxide can be detected as reaction product in the gas phase and that Fe polymeric film shows a turnover number of 9.18, while the Zn film shows a value of 2.74, corroborating the poor activity observed in cyclic voltammetry. © 2014 Taylor & Francis.